Polymer stealthing and mucin-1 retargeting for enhanced pharmacokinetics of an oncolytic vaccinia virus - Hill, C; Grundy, M; Bau, L; Wallington, S; Balkaran, J; Ramos, V; Fisher, K; Seymour, L; Coussios, C; Carlisle, RC (Cell Press, 2021)
Vaccinia Virus (VV) is a powerful tool for cancer treatment with the potential for tumour tropism, efficient cell-to-cell spread, rapid replication in cancer cells and stimulation of anti-tumour immunity. It has a well-defined safety profile and is being assessed in late-stage clinical trials. However, VV clinical utility is limited by rapid bloodstream neutralization and poor penetration into tumours. These factors have often restricted its route of delivery to intratumoural or intrahepatic artery injection, and may impede repeat dosing. Chemical stealthing improves the pharmacokinetics of non-enveloped viruses, but has not yet been applied to enveloped viruses like VV. Here amphiphilic polymer was used to coat VV, leading to reduced binding of a neutralising anti-VV antibody, (81.8% of polymer coated VV (PCVV) staining positive vs 97.1% of VV (p=0.0038)). Attachment of anti-Mucin-1 (aMUC1) targeting antibody, to give aMUC1-PCVV, enabled binding of the construct to MUC1. In high MUC1 expressing CAPAN-2 cells, infection with PCVV was reduced compared to VV, while infection was restored with aMUC1-PCVV. Pharmacokinetics of aMUC1-PCVV, PCVV and VV were evaluated. After IV injection of 1x108 viral genomes (VG) or 5x108 VG, circulation time for PCVV and aMUC1-PCVV was increased, with ∼5-fold higher circulating dose at 5 min vs VV.